24 Myocardial tissue characterisation in progressive CKD: is diffuse interstitial fibrosis the key intermediary of uraemic cardiomyopathy?. (May 2018) - Hayer, Manvir Kaur; Price, Anna M; Liu, Boyang; Baig, Shanat; Ferro, Charles J; Townend, Jonathan N; Steeds, Richard P; Edwards, Nicola C
Abstract : Introduction: Diffuse interstitial fibrosis (DIF) is present in early stage (eGFR <75 ml/min/1.73 m 2 ) chronic kidney disease (CKD) and is associated with abnormal myocardial contractility. It is not known whether there is a graded relationship with declining renal function. Methods: 119 patients with CKD; stage 2–4 (eGFR 89–15 ml/min/1.72 m 2 ) and stage 5 (pre-dialysis n=23, dialysis (CKD 5D) n=16) underwent CMR (1.5 T). T1 mapping (MOLLI), extracellular volume (ECV) and T2 mapping (T2-prepared SSFP) were used as markers of interstitial fibrosis and myocardial free water content respectively (MyoMaps, Siemens). Gadolinium was given if eGFR >30 ml/min/1.73 m 2 . Subjects with diabetes or known CV disease were excluded and asymptomatic ischaemic heart disease was excluded on exercise stress echocardiography. Results: Native septal myocardial T1, T2, LV volumes, LV mass and NT-proBNP increased with worsening renal function. Myocardial T1 time was inversely associated with: eGFR r=−0.344, p<0.001, and haematocrit r=−0.374, p<0.001, and directly with indexed LV mass r=0.345, p<0.001, T2 time r=0.673, p<0.001 and NT-proBNP r=0.375, p<0.001. LV mass (p=0.876) and T2 times (p=0.074 ) were unchanged between CKD stages 2–4 despite an increase in T1 (r=−0.274, p=0.017). In CKD 5, there was no difference in T1 and T2 times with dialysis but LV mass was higher (100±42 g/m 2 vs 73±16 g/m 2, p=0.034). Conclusion: An inverse graded relationship between myocardial T1 time and eGFR supports the concept of increasing DIF with deteriorating renal function, which precedes the development of elevated LV mass seen in CKD 5D. Myocardial water content is higher in CKD 5 irrespective of dialysis suggesting further changes in myocardial composition.